P220 Long-term safety profile of upadacitinib in patients with rheumatoid arthritis, psoriatic arthritis, or ankylosing spondylitis. (23rd April 2022) - Shaw, Tim; Burmester, Gerd R; Cohen, Stanley B; Winthrop, Kevin; Nash, Peter; Rubbert-Roth, Andrea; Deodhar, Atul; Elkayam, Ori; Mysler, Eduardo; Tanaka, Yoshiya; Liu, Jianzhong; Lacerda, Ana Paula; et al.
Abstract: Background/Aims: The objective of this analysis is to describe the long-term safety profile of upadacitinib (UPA) across rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) from the SELECT clinical program. Methods: Safety data (cut-off: 30 June 2020) from the UPA SELECT clinical program were compiled for RA (six trials), PsA (two trials), and AS (one trial) for this analysis. Treatment-emergent adverse events (TEAEs; onset on or after first dose and ≤30 days after last dose for UPA and methotrexate [MTX] or ≤ 70 days for adalimumab [ADA]) were summarized for RA (pooled UPA 15 mg once daily [QD], ADA 40 mg every other week [EOW], and MTX), PsA (pooled UPA 15 mg QD and ADA 40 mg EOW), and AS (UPA 15 mg QD). TEAEs are reported as exposure-adjusted adverse event rates (EAERs; events/100 patient-years [E/100 PY]). Results: In total, 4298 patients (RA, N = 3209; PsA, N = 907; AS, N = 182) received ≥1 dose of UPA 15 mg, totaling 8562 PY of exposure, with the majority of exposure from RA studies. AEs leading to discontinuation were generally similar across all treatment groups (UPA, ADA, and MTX) and patient populations (RA, PsA, and AS). The most common adverse events leading to discontinuation with UPA were pneumonia (RA), psoriatic arthropathy flare or worsening (PsA), and headache (AS). Rates of serious infection and opportunistic infection were generally similar across all treatment groups within each population and across RA, PsA, and AS. Pneumonia was both the most common serious infection and serious AE in RA and PsA. No serious infections were reported in patients with AS. Herpes zoster and increased CPK were reported more often with UPA compared to ADA or MTX, with UPA showing similar rates of herpes zoster across RA, PsA, and AS. Malignancies excluding NMSC were reported at similar rates across all treatment groups and populations. NMSC was not common, with numerically higher rates observed with UPA versus MTX and/or ADA in RA and PsA. Similar rates of adjudicated major adverse cardiovascular events (MACE) and adjudicated venous thromboembolic events (VTE) were observed across all treatment groups, with no events reported in patients with AS. Rates of death reported in these clinical studies were not higher than expected in the general populations. As anticipated for the patient populations, the most common cause of death observed was cardiovascular in nature. Conclusion: With the exception of herpes zoster, exposure-adjusted adverse event rates were generally similar across UPA, ADA, and MTX in RA, as well as UPA and ADA in PsA. No new safety risks were identified with long-term treatment in RA, PsA, or AS. UPA 15 mg demonstrated a consistent safety profile across RA, PsA, and AS populations in the SELECT clinical program. Disclosure: T. Shaw: Shareholder/stock ownership; T.S. is an employee of AbbVie and may hold stock or options. G.R. Burmester: Consultancies; G.R.B. has received consulting fees from AbbVie, Eli Lilly, Galapagos, Janssen, MSD, Pfizer, Roche, and UCB. Member of speakers' bureau; G.R.B. has received speakers fees from AbbVie, Eli Lilly, Galapagos, Janssen, MSD, Pfizer, Roche, and UCB. S.B. Cohen: Consultancies; S.B.C. has received consulting fees from AbbVie, Amgen, Boehringer Ingelheim, Gilead, Pfizer, Roche, and Sandoz. Grants/research support; S.B.C. has received research grants from AbbVie, Amgen, Boehringer Ingelheim, Gilead, Pfizer, Roche, and Sandoz. K. Winthrop: Consultancies; K.W. has received consulting fees from UCB Pharma, Pfizer, Bristol-Myers Squibb, Eli Lilly, AbbVie, Gilead, Galapagos, and Roche. Grants/research support; K.W. has received research grants from UCB Pharma, Pfizer, Bristol-Myers Squibb, Eli Lilly, AbbVie, Gilead, Galapagos, and Roche. P. Nash: Honoraria; P.N. has received honoraria for lectures and advice on behalf of AbbVie, BMS, Pfizer, Gilead/Galapagos, Sanofi, Celgene, Novartis, Lilly, Janssen, UCB, Samsung, MSD, Roche. Grants/research support; P.N. has received research funding for clinical trials from of AbbVie, BMS, Pfizer, Gilead/Galapagos, Sanofi, Celgene, Novartis, Lilly, Janssen, UCB, Samsung, MSD, and Roche. A. Rubbert-Roth: Honoraria; A. Rubbert-Roth has received honoraria for lectures and consulting from AbbVie, BMS, Chugai, Roche, Gilead, Janssen, Lilly, Sanofi, Amgen, Novartis. A. Deodhar: Consultancies; A.D. has received consultancy fees from Novartis, Pfizer, AbbVie, Eli-Lilly, UBC Pharma, GlaxoSmithKline, Galapagos, Janssen, Boehringer Ingelheim, Celgene. Grants/research support; A.D. has received research grants from Novartis, Pfizer, AbbVie, Eli-Lilly, UBC Pharma, GlaxoSmithKline. Other; A.D. has received fees for medical writing support provided from Novartis, Pfizer, AbbVie, Eli-Lilly, UBC Pharma, Galapagos, Janssen, Amgen. O. Elkayam: Consultancies; O.E. has received fees for serving as a consultant to AbbVie. Member of speakers' bureau; O.E. has received speaker fees on behalf of AbbVie. Grants/research support; O.E. has received research funding from AbbVie. E. Mysler: Consultancies; E.M. has received consultancy fees on behalf of AbbVie, AstraZeneca, Lilly, Pfizer, Roche, Janssen, GlaxoSmithKline, BMS, Sandoz. Grants/research support; E.M. has received grant/research support from AbbVie, AstraZeneca, Lilly, Pfizer, Roche, Janssen, GlaxoSmithKline, BMS, Sandoz. Y. Tanaka: Honoraria; Y.T. has received honoraria from Daiichi-Sankyo, Eli Lilly, Novartis, YL Biologics, Bristol-Myers, Eisai, AbbVie, Astellas, Pfizer, Sanofi, Asahi-kasei, GlaxoSmithKline, Mitsubishi-Tanabe, Gilead, Janssen, Chugai. Member of speakers' bureau; Y.T. has received speaking fees from Daiichi-Sankyo, Eli Lilly, Novartis, YL Biologics, Bristol-Myers, Eisai, AbbVie, Astellas, Pfizer, Sanofi, Asahi-kasei, GlaxoSmithKline, Mitsubishi-Tanabe, Gilead, Janssen, Chugai. Grants/research support; Y.T. has received research grants from Abbvie, Mitsubishi-Tanabe, Chugai, Asahi-Kasei, Eisai, Takeda, Daiichi-Sankyo. J. Liu: Shareholder/stock ownership; J.L. is an employee of AbbVie and may hold stock or options. A. Lacerda: Shareholder/stock ownership; A.L. is an employee of AbbVie and may hold stock or options. B.J. Pierre-Louis: Shareholder/stock ownership; B.PL. is an employee of AbbVie and may hold stock or options. P.J. Mease: Consultancies; P.J.M. has received consultation fee on behalf of AbbVie, Aclaris, Amgen, BMS, Boehringer Ingelheim, Celgene, Galapagos, Gilead, GlaxoSmithKline, Inmagene, Janssen, Novartis, Pfizer, SUN, UCB. Honoraria; P.J.M. has received honoraria from AbbVie, Aclaris, Amgen, BMS, Boehringer Ingelheim, Celgene, Galapagos, Gilead, GlaxoSmithKline, Inmagene, Janssen, Novartis, Pfizer, SUN, UCB. Grants/research support; P.J.M. has received research grants from Abbvie, Aclaris, Amgen, BMS, Boehringer Ingelheim, Celgene, Galapagos, Gilead, GlaxoSmithKline, Inmagene, Janssen, Novartis, Pfizer, SUN, UCB.